Effect of Backing Material and Clamping System on the Tensile Strength Of Dissimilar AA7075-AA2024 Friction Stir Welds - Mohammed, M. Hasan; M., Ishak; M. R. M., Rejab (Springer London, 2017)
Friction stir welding of dissimilar aluminum alloys has become an important application in the modern industries. Joint strength is a major consideration in this advanced technology. This paper presents an attempt made to improve the weld tensile strength by controlling the temperature distribution during the joining process. High-strength AA7075-T651 and AA2024-T351 aluminum alloys were friction stir welded using different backing and clamping materials. The tool rotation rate was preliminarily investigated to estimate the optimal spindle speed. Next, three composite backing plates and clamping systems were tested in conjunction with varying levels of traverse speeds and materials position. The transient temperatures were experimentally measured at different distances from the welding line. Asymmetric temperature distributions were observed with maximum records on the advancing side of the weld. Moreover, the influence of backing and cover materials on the joint strength was found to be varied with the applied level of the welding traverse speed. Based on these results, an idea to use asymmetric system of backing and cover materials was inspired. This system assisted to improve the temperature distribution and resulted in a sound weld with higher tensile strength. The detailed results of this work were discussed and the main outputs were outlined in the conclusions.